"Ou fazemos eleições limpas no Brasil ou não temos eleições" : uma investigação sobre a desinformação acerca do processo eleitoral brasileiro na perspectiva da análise dialógica do discurso - Queiroz, Thiago Felinto Oliveira de (2024)
This paper, based on the philosophy of the language of the Bakhtin circle, aims to understand how the discourses of misinformation about the electoral system constitute and function as discursive genres in order to elaborate a network of meaning assumed as true by those subjects. Considering that misinformation discourses are not an entirely new phenomenon, this research is guided by its chain with the problem of misinformation, considering the political context and social media platforms in the analysis. Thus, this research analyses the false discourses related to the Brazilian electoral system, which circulated on social media platforms in 2022 and were properly verified by fact-checking agencies. As a methodological orientation, this research was based on the Bakhtinian perspective of language, analyzing the corpus according to the category of discursive genres, using other notions of the Dialogical Analysis to complement the discussion. This study is characterized as an exploratory, qualitative, documentary, and theoretical research, aiming at the analysis of a corpus not yet analytically treated. As a result, the research identified a text categorized as a “denunciation message”, two texts identified as “denunciation post” and a fourth text evaluated as “digital press news”. The research concluded that the misinformation utterances are inherently ideological discursive manifestations that materialize themselves in various genres depending on the public with which they dialogue, and the effects intended by the author. Such texts reflect a political environment marked by the disrespect for institutions and the pursuit of power at any cost. In addition to harmful to democracy, such discourses foster an antagonism among citizens and generate obstruction to achieve true information.